Numerical linear algebra in signals, systems and control - Dooren, Paul van.; SpringerLink (Online service). (Dordrecht New York Springer, 2011)
The purpose of Numerical Linear Algebra in Signals, Systems and Control is to present an interdisciplinary book, blending linear and numerical linear algebra with three major areas of electrical engineering: Signal and Image Processing, and Control Systems and Circuit Theory. Numerical Linear Algebra in Signals, Systems and Control will contain articles, both the state-of-the-art surveys and technical papers, on theory, computations, and applications addressing significant new developments in these areas. The goal of the volume is to provide authoritative and accessible accounts of the fast-paced developments in computational mathematics, scientific computing, and computational engineering methods, applications, and algorithms. The state-of-the-art surveys will benefit, in particular, beginning researchers, graduate students, and those contemplating to start a new direction of research in these areas. A more general goal is to foster effective communications and exchange of information between various scientific and engineering communities with mutual interests in concepts, computations, and workable, reliable practices.
1 The Anti-Reflective Transform and Regularization by Filtering; A. Aricò, et al -- 2 Classifications of Recurrence Relations; T. Bella, et al -- 3 Partial Stabilization of Descriptor Systems; P.Benner -- 4 Comparing Two Matrices by Means of Isometric Projections; T. P. Cason, et al -- 5 A Framelet-Based Algorithm for Video Enhancement; R. H. Chan, et al -- 6 Perturbation Analysis of the Mixed-Type Lyapunov Equation; M.Cheng and S.Xu -- 7 Numerical and Symbolical Methods; D. Christou, et al -- 8 Numerical Computation of the Fixed Poles; D.Chu and Y. S. Hung -- 9 Robust Control of Discrete Linear Repetitive Processes; B. Cichy, et al -- 10 Unique Full-Rank Solution of the Sylvester-Observer Equation; K.Datta and M. Thapa -- 11 On Symmetric and Skew-Symmetric Solutions to a Procrustes Problem; Y.-B. Deng and D. Boley -- 12 Some Inverse Eigenvalue and Pole Placement Problems; S. Elhay -- 13 Descent Methods for Nonnegative Matrix Factorization; Ngoc-Diep Ho et al -- 14 A Computational Method for Symmetric Stein Matrix Equations; K. Jbilou and A. Messaoudi -- 15 Optimal Control for Linear Descriptor Systems; P. Kunkel and V. Mehrmann -- 16 Robust Pole Assignment; Tiexiang Li, et al -- 17 Synthesis of Fixed Structure Controllers; W.A. Malik, et al -- 18 A Secant Method for Nonlinear Matrix Problems; M. Monsalve and M. Raydan -- 19 On FastICA Algorithms and Some Generalisations; H. Shen, et al -- 20 On Computing Minimal Proper Nullspace Bases; Andras Varga -- 21 Optimal Control of Switched System; C. Z. Wu, et al.
Electronic reproduction.
Keywords: Algebras, Linear; Engineering mathematics; Electronic books